2017
DOI: 10.1111/pbi.12750
|View full text |Cite
|
Sign up to set email alerts
|

The association of hormone signalling genes, transcription and changes in shoot anatomy during moso bamboo growth

Abstract: SummaryMoso bamboo is a large, woody bamboo with the highest ecological, economic and cultural value of all the bamboo types and accounts for up to 70% of the total area of bamboo grown. However, the spatiotemporal variation role of moso bamboo shoot during growth period is still unclear. We found that the bamboo shoot growth can be divided into three distinct periods, including winter growth, early growth and late growth based on gene expression and anatomy. In the early growth period, lateral buds germinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
116
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 44 publications
1
116
0
Order By: Relevance
“…As the rapid-growth of bamboo shoots is largely determined by phytohormone and nutrients [2, 27], and we have demonstrated that PeGATAs are differentially expressed in rhizome tissues and under GA treatment (Fig. 7a, b), we hypothesized that PeGATAs may also be involved in fast-growing bamboo shoots.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the rapid-growth of bamboo shoots is largely determined by phytohormone and nutrients [2, 27], and we have demonstrated that PeGATAs are differentially expressed in rhizome tissues and under GA treatment (Fig. 7a, b), we hypothesized that PeGATAs may also be involved in fast-growing bamboo shoots.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that several gene families are involved in flower development and abiotic stress [3032, 41], the rapid-growth associated transcription factors remain elusive. The genome sequences of moso bamboo[33] and transcriptome studies [2, 27, 28, 40] provide important platforms for the identification of rapid-growth shoot and rhizome development associated gene families. The rapid-growth related genes could provide useful information for genetic manipulation of plant height in future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a long time, the molecular research of bamboo mainly follows the studies of model plants (Wei et al, 2013). Recently, with the advancement of next generation sequencing technologies, several studies have reported to explore bamboo transcriptome profiles in several important biological processes such as fast growth, flowering and primary thickening growth (Gao et al, 2014;He et al, 2013;Li et al, 2018;Liu et al, 2012;Peng et al, 2013;Shih et al, 2014;Wei et al, 2017Wei et al, , 2018Zhang et al, 2012). Meanwhile, the genetic transformation system of bamboo has been successfully established (Qiao et al, 2014;Ye et al, 2017), and several groups have made progress in increasing the callus regeneration efficiency, which is important for establishing an efficient transgenic system of bamboo (Wei et al, 2015).…”
Section: Introductionmentioning
confidence: 99%